The 24‐month course of manic symptoms in children. (26th June 2013) - Findling, Robert L; Jo, Booil; Frazier, Thomas W; Youngstrom, Eric A; Demeter, Christine A; Fristad, Mary A; Birmaher, Boris; Kowatch, Robert A; Arnold, Eugene; Axelson, David A; Ryan, Neal; Hauser, Jessica C; et al.
Abstract : Objectives: The Longitudinal Assessment of Manic Symptoms (LAMS) study was designed to investigate phenomenology and establish predictors of functional outcomes in children with elevated manic symptoms. The purpose of this series of analyses was to determine whether the participants demonstrated different trajectories of parent‐reported manic and biphasic symptoms over the first 24 months of follow‐up and to describe the clinical characteristics of the trajectories. Methods: The 707 participants were initially aged 6–12 years and ascertained from outpatient clinics associated with the four university‐affiliated LAMS sites. There were 621 children whose parents/guardians' ratings scored ≥ 12 on the Parent General Behavior Inventory–10‐item Mania Form (PGBI‐10M) and a matched random sample of 86 children whose parents/guardians' ratings scored ≤ 11 on the PGBI‐10M. Participants were seen every six months after the baseline and their parents completed the PGBI‐10M at each visit. Results: For the whole sample, manic symptoms decreased over 24 months (linear effect B  =   −1.15, standard error = 0.32, t  =   −3.66, p < 0.001). Growth mixture modeling revealed four unique trajectories of manic symptoms. Approximately 85% of the cohort belonged to two classes in which manic symptoms decreased. The remaining ~15% formed two classes ( high and rising and unstable ) characterized by the highest rates of diagnostic conversion to a bipolar disorder (all p‐values < 0.001). Conclusions: Outcomes are not uniform among children with symptoms of mania or at high risk for mania. A substantial minority of clinically referred children shows unstable or steadily increasing manic symptoms, and these patterns have distinct clinical correlates.